High Temperature Corrosion Study on NiCr Coated Low Alloy and Mild Steel - Kumar, Jitendra; Kushwaha, Anshika; Rajput, Sunil Kumar; Soota, Tarun (International Journal of Integrated Engineering, 2024)
Cyclic hot corrosion behaviour of bare and D-gun sprayed NiCr coated low alloy and mild steel sample having dissimilar coating thicknesses viz. 0.2-0.25 mm and 0.25-0.30 mm have been studied in molten salt environment mixture of Na2SO4 - 25wt. % NaCl at temperature of 750?C. Corrosion kinetics were analysed and parabolic rate constants (Kp) for both bare and coated sample were calculated  and observed that 0.2-0.25 mm thick NiCr coated specimen showed better resistance against high temperature corrosion for both materials. SEM/EDX analysis was carried out to examine scale formed on the bare and coated Sample after hot corrosion.